Jurisdiction in Lawsuits for Damages Arising From Artificial Intelligence Systems under Jordanian and Iraqi Law - Shihab, Noor Al-Huda; Juma, Abdulrahman (Journal of Legal Sciences, 2026)
This study aimed to clarify the nature of civil actions and their role in resolving disputes related to jurisdiction over damages arising from artificial intelligence (Ai) systems, as well as to analyze the role of the judiciary in adjudicating such disputes and the legal foundations on which it relies. The researcher adopted both analytical and comparative methodologies and concluded that the “human proxy” theory represents one of the most prominent modern legal approaches to addressing the liability gap in cases where it is difficult to attribute harm to a specific natural person. this theory assigns liability to a natural person connected to the intelligent system—such as the designer, developer, or end-user—acting as a legal representative for the Ai entity, which lacks legal personality. This approach contributes to establishing clear legal liability and providing effective protection for injured parties.The study also revealed the inadequacy of traditional means of proof, such as testimony, presumptions, and written evidence, in light of the rapid advancement of Ai technologies—particularly in cases where the source or mechanism of the harm is difficult to trace due to the complexity of algorithms and the autonomous decision-making of these systems. The study concluded that it is essential to develop the civil evidentiary system to keep pace with the digital transformation and recommended enacting a specific law on Ai ethics in Iraq, incorporating principles for the design, development, and use of intelligent systems while ensuring respect for human rights, privacy, and human dignity. it also called for the adoption of a unified international convention on ai-related damages, through cooperation between national legislations and international organizations, with active participation from major countries and the support of the united nations and Enesco, to standardize legal and ethical frameworks in this field.